6-3x=7x+14

Simple and best practice solution for 6-3x=7x+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-3x=7x+14 equation:


Simplifying
6 + -3x = 7x + 14

Reorder the terms:
6 + -3x = 14 + 7x

Solving
6 + -3x = 14 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
6 + -3x + -7x = 14 + 7x + -7x

Combine like terms: -3x + -7x = -10x
6 + -10x = 14 + 7x + -7x

Combine like terms: 7x + -7x = 0
6 + -10x = 14 + 0
6 + -10x = 14

Add '-6' to each side of the equation.
6 + -6 + -10x = 14 + -6

Combine like terms: 6 + -6 = 0
0 + -10x = 14 + -6
-10x = 14 + -6

Combine like terms: 14 + -6 = 8
-10x = 8

Divide each side by '-10'.
x = -0.8

Simplifying
x = -0.8

See similar equations:

| (3+x)=1 | | 2x+66=7x-34 | | 7x+169=5x+153 | | (6x+14)+11= | | -14+10x=9x+23 | | (6x*14)+11= | | 3(x+4)+15=36 | | 8(9+3x)+11= | | 4q/5+6=18 | | (5x-9)+9= | | 4q/5+6=188 | | y=(2e^2t)+4 | | -6v-6=-3(v+6) | | 4x^2-29+x^2-15+x^2+8=180 | | (18x+13)-7x= | | 2.5w-1,3w=14.4 | | 8x-1=6x+9 | | (x+7)=15 | | 3(x-5)+14(x+6)= | | 4(3x+12)+14x-13= | | 8(u+6)=-5u-17 | | 2.5w-1.3w=14.4 | | 9x+4+4x-5=90 | | (5x+12)+(8x-5)= | | 9v-43=2(v+3) | | w/15.36=6 | | (x-4)=13 | | -7x-87=-14x+39 | | 18x=48+12x | | -4*-4*-4=x | | 5x-10+2x+9=90 | | 4x1/12 |

Equations solver categories